1988
DOI: 10.1002/j.1460-2075.1988.tb02826.x
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome region containing the highly polymorphic HLA class I genes displays limited large scale variability in the human population.

Abstract: The large-scale organization and polymorphism of the HLA class I region was investigated by pulsed field gel (PFG) fractionation of DNA from various HLA-typed cell lines cleaved by different 'rare cutter' restriction enzymes, followed by hybridization with 'general' and locus-specific HLA probes. Results indicate that (i) most HLA class I sequences are contained in a 340 kb MluI DNA fragment which also carries the HLA-A gene; (ii) HLA-A, -B and -C genes are present on different fragments bounded by 'HTF island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
1

Year Published

1990
1990
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
(24 reference statements)
3
10
1
Order By: Relevance
“…3), a distance consistent with that proposed by previous pulsed-field mapping experiments (1-3, 15, 16). As observed in studies using isolated cosmid clones, both loci are associated with CpG islands, with the islands marking the 5' end of each class I gene (15,16). Together with our data this indicates that each gene is located telomeric of these islands and transcribed in a centromeric-to-telomeric orientation.…”
supporting
confidence: 89%
“…3), a distance consistent with that proposed by previous pulsed-field mapping experiments (1-3, 15, 16). As observed in studies using isolated cosmid clones, both loci are associated with CpG islands, with the islands marking the 5' end of each class I gene (15,16). Together with our data this indicates that each gene is located telomeric of these islands and transcribed in a centromeric-to-telomeric orientation.…”
supporting
confidence: 89%
“…Few probes were available for analysis of this region and were essentially the class I genes themselves or sequences very close to them. During a previous study on the structure of the HLA class I region, we found differences in the size of haplotype HLA-A24 (in relation to the other six that were tested; Chimini et al 1988). Similar reports have shown differences in size for haplotype A31 (Lord et al 1990).…”
Section: Introductionsupporting
confidence: 57%
“…Preparation of high relative mass DNA in agarose blocks from cultured cells, restriction digests, transfer onto nylon membranes, and hybridization were essentially as previously described (Carle and Olson 1984;Van Ommen and Verkerk 1986;Chimini et al 1988). Five rare cutter enzymes were used: Not I, Mlu I, Nru I, Sal I, and Sfi I in single or double digestion.…”
Section: Methodsmentioning
confidence: 99%
“…It contains more than 50 genes in about 4 million base pairs (bp) of DNA (1). The organization of the genes has been determined by a combination of techniques including recombination analysis, cosmid walking, and pulsed-field gel electrophoresis (PFGE) (2)(3)(4)(5). The telomeric end of the MHC contains the class I genes (6) and the centromeric end the class II genes (7).…”
mentioning
confidence: 99%